University digital infrastructure and student-driven innovation: Evidence from higher education institutions in Shandong, China - Xinyu, Li; Hussin, Wan Nur Tasnim Wan (Edelweiss Applied Science and Technology, 2026)
The rapid advancement of digital transformation in higher education has reshaped innovation ecosystems within universities. However, limited empirical research has examined how university digital infrastructure influences student-driven innovation and through what mechanisms this relationship operates. Drawing on the resource-based view and organizational support theory, this study investigates the direct effect of university digital infrastructure (UDI) on student-driven innovation (SDI) and the mediating role of institutional research support (IRS) within universities in Shandong Province, China. Using survey data collected from university students and employing structural equation modeling (SEM) for hypothesis testing, the results demonstrate that university digital infrastructure significantly and positively affects student-driven innovation. Furthermore, digital infrastructure is found to significantly enhance institutional research support. Most importantly, institutional research support partially mediates the relationship between digital infrastructure and student-driven innovation, indicating that digital platforms foster innovation not only directly but also indirectly through strengthening research support systems. These findings contribute to the literature by extending digital infrastructure research into the higher education innovation context and clarifying the internal mechanism linking digital resources to student innovation outcomes. Practically, the study provides policy implications for universities seeking to enhance innovation capacity through strategic digital infrastructure investment and institutional research support enhancement.